Exploring the Barriers and Enablers to High Quality Clinical Placements in Physiotherapy at a Metropolitan Teaching Hospital Using an Implementation Science Approach - Joanna Hargreaves; Simone Leslie; Michelle Cottrell; Ashlee Snoswell; Shaun O'Leary; Peter Window (Bond University, 2023)
_Background_: Indicators of quality in physiotherapy clinical placements offer opportunity to assess current practise. The Consolidated Framework for Implementation Research (CFIR) provides a framework to identify barriers and enablers to guide tailored strategies for improvement. _Aims_: The aims of this study were to explore adherence to indicators of quality in a single physiotherapy department at a metropolitan teaching hospital, and to conceptualise the barriers and enablers to achieving quality in clinical placements in this context using the CFIR. _Methods_: A mixed-methods sequential explanatory study design was undertaken at a metropolitan hospital in Queensland, Australia. Stakeholder's perceptions of enablers and barriers to meeting quality indicators in relation to current practise were assessed using a standardised survey (n=28), followed by focus groups and semi-structured interviews (n=19). _Results_: Three main themes were identified: (i) training in clinical education skills is essential but currently focuses on assessment, (ii) the clinical educator (CE) role is perceived as having low value, and (iii) opportunities identified to develop existing supports for CEs. _Conclusion_: Findings from this study have informed strategies implemented at the facility under study, which focus on increasing the perceived value of the CE role, engaging CEs in training as educators, and collaboration with university coordinators.